Bhopal, Dunsmuir and TRPA1: what they have taught us about nociception - Shusterman, Dennis J.; Salmon, Andrew G. (Frontiers in Allergy, 2025)
On separate occasions nearly a decade apart, two large-scale accidental releases of industrial chemicals exposed substantial “bystander” (non-worker) populations to highly toxic air pollutants. The first of these events, occurring in Bhopal, India in 1984, generated worldwide attention and concern given its geographic scope and significant lethality. The second incident, occurring in Dunsmuir, CA in 1991 – while less publicized – yielded new insights into the pathogenesis of irritant-induced asthma. Linking these events is the fact that the toxicants involved – methyl isocyanate (MIC) in Bhopal and methyl isothiocyanate (MITC) in Dunsmuir – preferentially bind to the same TRPA1 nociceptive ion channel. This review examines each of these exposure events, including their mechanistic implications for anticipating (and potentially preventing) future long-term health effects from accidental chemical exposures.